Dukungan Keluarga terhadap Kesehatan Mental Lansia selama Pandemi COVID-19 di Kota Tangerang Selatan: Dukungan Keluarga terhadap Kesehatan Mental Lansia selama Pandemi COVID-19 di Kota Tangerang Selatan - Sahwati, Sahwati; Istifada, Rizkiyani; Nuraeni, Eni (Jurnal Kesehatan Masa Depan, 2024)
Life expectancy increases and positively impacts if there is good treatment for the elderly. The decline in the health status of the elderly during the COVID-19 pandemic is one of the consequences that cause the elderly to have a poor quality of life. Mental health problems are also significant issues during a pandemic. Family is one of the most important factors for maintaining the mental health of the elderly during the COVID-19 pandemic. This study aims to determine the relationship between family support and mental health in the elderly during the Covid-19 pandemic in South Tangerang City. The research design used is descriptive-analytic with a cross-sectional approach. The research used Adaptation, Partnership, Growth, Affection, Resolve (APGAR), and Self Reporting Questionnaire (SRQ) questionnaires for collecting data. The sample of this study amounted to 174 respondents by convenience sampling technique. The inclusion criteria of respondents in this study were (1) elderly aged ³ 60 years in good health or with comorbidities; (2) elderly who still communicate with their family. The results of this study indicate that the elderly have positive family support as many as 142 respondents (81.6%), and the elderly have undisturbed mental health of 142 respondents (81.6%). The Chi-Square statistical test results show a relationship between family support and mental health in the elderly during the COVID-19 pandemic in South Tangerang City (p-value = 0.000). The current COVID-19 pandemic has a threatening impact on the health status of the elderly, so there is a need for family support to maintain the mental health of the elderly. Integrated Community Health Service of the Elderly is expected to provide health education actively about the importance of family support for the mental health of the elderly.